Psychological Characteristics and Cognitive Intervention of Flow State in Sports - Lin Du; Shuyun Zhu; Changshan Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This article explored how athletes' performance is influenced by their flow state, suggesting cognitive interventions to enhance their experiences and improve performance. The experiment recruited 120 athletes, covering various sports such as basketball, soccer, volleyball, table tennis, sprinting, long jump, high jump, swimming, and weightlifting, yielding 100 valid questionnaires were obtained. Athletes' flow states, measured by the Flow State Scale (FSS), showed connections with psychological traits. Tailored cognitive interventions improved athletes' flow states, leading to significant enhancements in FSS scores and overall sports performance. The research findings indicate that using cognitive intervention methods to enhance athletes' flow states not only improves their skill performance but also provides valuable insights for enhancing sports training methods and psychological intervention policies, thereby promoting athletes to better unleash their potential and elevate the overall level of competition.